ANALISIS KEDUDUKAN ANAK HASIL PERKAWINAN CAMPURAN ANTARA WARGA NEGARA INDONESIA DAN WARGA NEGARA ASING - RISTI DWI RAMASARI (KEADILAN PROGRESIF, 2018)
Mixed marriage is basically a marriage conducted by people of different nationalities, one of whom is an Indonesian citizen. The result of a mixed marriage for a child is obtaining the citizenship of the father or from his mother and the child's right to inheritance in the event of a divorce between his parents. The problem of this research is "How is the position of child of mixed marriage between Indonesian citizen and foreign citizen?" The problem approach in this research uses normative juridical approach and empirical approach. Data collection was done by literature study and field study and then analyzed by qualitative juridical. The results of this study indicate the position of the child of the result of mixed marriage according to Law Number 12 Year 2006 concerning the Citizenship of the Republic of Indonesia is a child born from the marriage of a woman Indonesian citizen and male Foreigner, as well as a child born of a marriage of a woman Foreign Citizen with male Indonesian citizen, equally recognized as an Indonesian citizen. The child will be a dual citizen, and after the child is 18 years old or married then he must make his choice. Statements to elect citizenship must be submitted no later than 3 (three) years after the child is 18 years of age or after marriage. This dual citizenship provides more legal protection for children resulting from mixed marriages.